Peningkatan Kinerja Guru dalam Penyusunan Perangkat Pembelajaran Melalui Pelaksanaan Supervisi Akademik dan In House Training - yunian, rizki wahyu; Hasanudin, Hasanudin; Rosidin, Undang; Hariri, Hasan; Sowiyah, Sowiyah (Universitas Islam Negeri Raden Intan Lampung, 2023)
Many teacher performance issues include: Implementation of learning that does not go according to plan; teacher performance in lesson planning is still intermediate and low; The subject of this study was his SMP teachers. The research method is school action research. Consistent with the results obtained, it can be concluded that educator performance in learning planning was significantly enhanced by optimizing academic supervision through group and individual techniques. Based on our findings:Document completeness increased from 50%, 88% to 94%. PTS is planning a 90% increase to meet document completeness success metrics and stop the cycle. and four predicates for performance evaluation in cycle I, the predicate distribution is: 0% not good, 42% pretty good, 58 good, 0% very good. In cycle II, the predicate distribution is:Poor 0%, Fairly Good 8, Good 42 to Very Good 49. Predicate Good and Very Good 42 + 49 = 91%. Therefore, we can say that the predicate performance distribution before the cycle increased in cycle I.